HIMPUNAN SEMI KONTINU DALAM RUANG TOPOLOGI - Djuwandi, Djuwandi (MATEMATIKA, 2011)
It should be noted to understand some material about the topology of real number, continuous function in topological spaces, open function, closed function in topological spaces. For semi-continous function expected to understand the concept of semi-open sets in topological spaces.